‘Moving forward’:: Honouring Ken’s legacy; Welcoming the new Board - Hewitt Evans, Joanna (European Journal for Qualitative Research in Psychotherapy, 2018)
Ken Evans founded the European Journal for Qualitative Research in Psychotherapy in 2006. Initially it was an Anglo/Norwegian collaboration between Ken, the Scarborough Psychotherapy Training Institute and Dan Van Baalen of the Norwegian Gestalt Institute. Later Ken hosted the journal through the European Centre for Psychotherapeutic Studies and became Chief Editor. Ken believed in the importance of qualitative research, that it shared the values of relational psychotherapy and was compatible philosophically. He felt it offered some sort of balance to the randomised clinical trials and evidence-based practice, so loved by fundholders. He wanted the journal to be freely and widely available.